Real‐world outcomes in cardiac resynchronization therapy patients: Primary results of the SMART registry - Ignacio García‐Bolao; Roy S. Gardner; Daniel Gras; Antonio D'Onofrio; George Mark; Devi Nair; Nicolas Lellouche; Miroslav Novak; Ronald Lo; Engwooi Chew; David Wright; Andrew Kaplan; et al. (ESC Heart Failure)
Abstract Aims Cardiac resynchronization therapy (CRT) is guideline recommended for the treatment of symptomatic heart failure (HF) with reduced left ventricular ejection fraction and prolonged QRS. However, patients with common comorbidities, such as persistent/permanent atrial fibrillation (AF), are often under‐represented in clinical trials. Methods The Strategic Management to Optimize Response to Cardiac Resynchronization Therapy (SMART) registry (NCT03075215) was a global, multicentre, registry that enrolled de novo CRT implants, or upgrade from pacemaker or implantable cardioverter defibrillator to CRT‐defibrillator (CRT‐D), using a quadripolar left ventricular lead in real‐world clinical practice. The primary endpoint was CRT response between baseline and 12 month follow‐up defined as a clinical composite score (CCS) consisting of all‐cause mortality, HF‐associated hospitalization, New York Heart Association (NYHA) class and quality of life global assessment. Results The registry enrolled 2035 patients, of which 1558 had completed CCS outcomes at 12 months. The patient cohort was 33.0% female, mean age at enrolment was 67.5 ± 10.4 years and the mean left ventricular ejection fraction was 29.6 ± 7.9%. Notably, there was a high prevalence of mildly symptomatic patients (NYHA class I/II 51.3%), non‐left bundle branch block (LBBB) morphology (38.0%), AF (37.2%) and diabetes mellitus (34.7%) at baseline. CCS at 12 months improved in 58.9% (n = 917) of patients; 20.1% (n = 313) of patients stabilized and 21.0% (n = 328) worsened. Several patient characteristics were associated with a lower likelihood of response to CRT including older age, ischaemic aetiology, renal dysfunction, AF, non‐LBBB morphology and diabetes. Higher HF hospitalization (P < 0.001) and all‐cause mortality (P < 0.001) were observed in patients with AF. These patients also had lower percentages of ventricular pacing than patients in sinus rhythm at baseline and follow‐up (P < 0.001, both). A further association between AF and non‐LBBB was observed with 81.4% of AF non‐LBBB patients experiencing an HF hospitalization compared with 92.5% of non‐AF LBBB patients (P < 0.001). Mortality between subgroups was also statistically significant (P = 0.019). Conclusions This large, global registry enrolled a CRT‐D population with higher incidence of comorbidities that have been historically underrepresented in clinical trials and provides new insight into factors influencing response to CRT. As defined by CCS, 58.9% of patients improved and 20.1% stabilized. Patients with AF had particularly worse clinical outcomes, higher HF hospitalization and mortality rates and lower percentages of ventricular pacing. High incidence of HF hospitalization in patients with AF and non‐LBBB in this real‐world cohort suggests that ablation may play an important role in increasing future CRT response rates.